Penanganan Sampah Laut di Indonesia : A Review - Fikry, Izzul; Putra, Riko Satrya Fajar Jaelani; Nindyapuspa, Ayu; Auliya, Prativi Khilyatul; Abdillah, Hayy Nur; Wuryaningrum, Nanda Dwi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Perkapalan Negeri Surabaya, 2024)
Indonesia produces 33,113,277.69 tons of waste per year, in which 13,455,925.41 tons are unmanaged waste. From these data, it can be seen that Indonesia is still experiencing problems in waste management. Unmanaged waste is at risk of being carried away by river currents that lead to the sea., Not only land-based waste, marine debris must also be adressed. Marine debris could possibly come from activities on land or at sea. Marine debris consists of three categories; macro, meso and micro marine debris. This paper is a narrative-review on how to dealt with marine debris in Indonesia. Several methods have been done by the Indonesian government to dealt with marine debris. In 2018, the Indonesian government issued Presidential regulation number 83 of 2018, concerning the handling of marine debris. Besides that, Indonesian government also formed National Plan of Action (NPOA) and opened itself to foreign investors to invest on that action plan, especially on adressing marine plastic debris. In addition to forming special team and supporting regulations, the complexity of marine debris problems must also be resolved by integrated research on marine debris, and also make changes on Indonesian human resources‘ mentality and mindset.